Implementasi MOORA dalam Sistem Pendukung Keputusan untuk Kata Kunci Iklan Terbaik Shopee menggunakan Looker Studio - Artha Mefia, Elsa Kirana; Saputra, Yogi; Suryana, Nana; Dauni, Popon; Arujisaputra, Erwin Teguh (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2025)
In an increasingly competitive digital era, PT Soka Cipta Niaga is required to optimize its marketing strategy through marketplace platforms such as Shopee. One of the main challenges in carrying out a marketing strategy on Shopee is the selection of the right keywords, because it can affect product visibility and the effectiveness of advertising costs. This study aims to help the process by applying the MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis) method in the decision support system. The MOORA method was chosen because it is able to evaluate various alternatives by objectively considering the criteria that are beneficial (benefit) and unprofitable (cost). The development of the system is carried out through structured stages using the waterfall approach, with the stages of needs analysis, design, implementation in the form of a dashboard looker studio, to the testing process using black box testing. Data were collected through observation, interviews, questionnaires, and literature studies. The result of this research is in the form of an interactive dashboard that not only displays keyword performance, but also provides the best keyword recommendations with three advanced groupings, namely prioritize and improve by 20%, maintain, and re-evaluate/reduce, based on the results of the MOORA method ranking. This system has been proven to provide more objective and consistent results compared to manual evaluations. Thus, this system can help PT Soka Cipta Niaga's digital marketing division in making decisions related to the selection of the best keywords more optimally.